Ultrastructure of spermiogenesis and spermatozoa of Gymnotus cf. anguillaris and Brachyhypopomus cf. pinnicaudatus (Teleostei : Gymnotiformes) - Franca, G. F.; Oliveira, C.; Quagio-Grassiotto, I. (Churchill Livingstone, 2007)
The ultrastructure of spermiogenic stages and spermatozoa of representatives of two gymnotiform families, Gymnotus cf. anguillaris (Gymnotidae) and Brachyhypopomus cf. pinnicaudatus (Hypopomidae) were studied. Spermiogenesis of both species is characterized by lateral development of the flagellum and formation of a nuclear fossa. Some differences were found between these species, such as whether (B. cf. pinnicaudatus) or not (G. cf. anguillaris) nuclear rotation occurs, permanence of the cytoplasmic channel, and type and localization of the nuclear fossa. In the G. cf anguillaris spermatozoon the nucleus is spherical with highly condensed chromatin. The nuclear fossa is shallow and lateral and is associated with the centriolar complex through stabilizing fibrils. The midpiece is short, with many vesicles, a cytoplasmic channel, and elongate mitochondria. In the B. cf. pinnicaudatus spermatozoon the ovoid nucleus is elongated lateral and posterior to the centriolar complex, and has highly condensed chromatin. The eccentric nuclear fossa is of the moderate type, and contains the entire centriolar complex. The midpiece is long, with numerous vesicles, elongate mitochondria, and no cytoplasmic channel. In both species the flagella are laterally disposed in relation to the nucleus and comprise of the classical 9 + 2 axoneme. Most of the characteristics found in the spermatozoa of these two species of Gymnotiformes are shared with species of Characiformes, whereas only a few are also found in Siluriformes. This suggests that Gymnotiformes and Characiformes may be more closely related than previously proposed. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: sperm; morphology; electron microscopy; fish evolution; knifefish